Geopolitik Indonesia dalam dinamika perebutan pengaruh kekuatan global - naqiya, sadiyana yaqutna (Maliki Interdisciplinary Journal, 2026)
Indonesia’s geopolitics in the dynamics of the struggle for global influence in the Indo-Pacific region. The shift in the world power structure towards a multipolar system has led to increased geopolitical competition between major powers such as the United States and China in the fields of economics, military, technology, and international diplomacy. Indonesia’s geographical position between two oceans and two continents makes Indonesia a strategic role in international trade and security routes. This study uses a qualitative descriptive method with a literature study approach to analyze Indonesia’s strategic position, the geopolitical challenges faced, and the strategies implemented to safeguard national interests. The results show that Indonesia faces various geopolitical challenges, such as maritime security threats, global economic competition, and non-traditional threats in the form of cyber attacks and disinformation. In facing these dynamics, Indonesia implements an independent and active foreign policy, strengthens multilateral diplomacy through ASEAN, and enhances its maritime defense strategy and the concept of the Global Maritime Axis. With this strategy, Indonesia strives to maintain national and regional stability without getting caught up in the rivalry of major world powers.